Research progress on tumor-infiltrating lymphocyte therapy for cervical cancer - Zhang, Wei; Liu, Yong-Min; Li, Dong; Liu, Shan; Cai, Xiao-Jun; Tang, Ji-Ying; Zuo, Zhi-Gang; Li, Xin-Hui; Zhao, Yi (Frontiers in Immunology, 2025)
Cervical cancer is a common malignant tumor in women, and human papillomavirus (HPV) infection is a major cause of cervical cancer. Tumor-infiltrating lymphocytes (TILs) are a heterogeneous group of lymphocytes primarily composed of T lymphocytes found within the tumor parenchyma and stroma. These cells can be isolated from tumor tissue, activated, expanded in vitro, and reinfused into the patient to exert an anti-tumor immune effect. As a form of personalized immunotherapy, TILs therapy has shown satisfactory efficacy and safety in advanced recurrent and metastatic cervical cancer, offering new hope to patients with advanced cervical cancer. However, TILs therapy for advanced cervical cancer still faces several limitations and challenges. This article reviews the process and latest developments in TILs therapy for advanced cervical cancer and discusses the challenges in the usage and prospects for this treatment.